2019
DOI: 10.1103/physrevlett.123.066401
|View full text |Cite
|
Sign up to set email alerts
|

K -Shell Core-Electron Excitations in Electronic Stopping of Protons in Water from First Principles

Abstract: Understanding the role of core electron excitation in liquid water under proton irradiation has become important due to the growing use of proton beams in radiation oncology. Using a firstprinciples, non-equilibrium simulation approach based on real-time time-dependent density functional theory, we determine the electronic stopping power, the velocity-dependent energy transfer rate from irradiating ions to electrons. The electronic stopping power curve agrees quantitatively with experimental data over the velo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 49 publications
1
58
0
Order By: Relevance
“…Yao et al demonstrated that, for protons in water, the ensemble average of S e (v p = 8.0 a.u.) based on 64 regularly distributed trajectories in a 16 Å-long water box converges very well to SRIM's data 23 . This value v p = 8 a.u.…”
Section: Please Cite This Articlementioning
confidence: 58%
See 4 more Smart Citations
“…Yao et al demonstrated that, for protons in water, the ensemble average of S e (v p = 8.0 a.u.) based on 64 regularly distributed trajectories in a 16 Å-long water box converges very well to SRIM's data 23 . This value v p = 8 a.u.…”
Section: Please Cite This Articlementioning
confidence: 58%
“…Local-orbital implementations, either numerical as in SIESTA 74 , or Gaussian basis functions as in CP2K and other codes 52,75 , are significantly more efficient provided a smart choice of basis set is made that captures the possibility of electrons being excited to high energy states or even ejected. Moreover, it has recently been shown that both valence and core electrons can contribute significantly to electronic stopping 23,30,51 .…”
Section: Theory and Methodsmentioning
confidence: 99%
See 3 more Smart Citations